ANALISIS KAPASITAS PETANI DALAM USAHATANI PADI SAWAH DI KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Nurhilal Nurhilal; Usman Rianse; Salahuddin Salahuddin; La Ode Kasno Arif; Arfiani Arfiani (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
This study aimed to analyze the capacity of farmers in paddy farming in Baruga Village, Baruga District, Kendari City. The population of this study was 280 paddy farmers. The sample of this study was 28 rice farmers (10% of the population) taken by simple random sampling. The data analysis of this study used descriptive statistics. Descriptive statistics to describe or describe the state of the research variables. The results of the study indicate that the capacity of farmers in paddy farming in Baruga Village, Baruga District, Kendari City is in the medium category. Paddy farmers in Baruga Village, Baruga District, Kendari City have had good capacity in rice farming from managerial, technical, and social aspects but need to be improved. The capacity of rice farmers from the managerial and technical capacity aspects is in the medium category. Meanwhile, the capacity of farmers from the social aspect is in the high category.